2001
DOI: 10.1590/s1517-86922001000400003
|View full text |Cite
|
Sign up to set email alerts
|

Estimativa da gordura corporal através de equipamentos de bioimpedância, dobras cutâneas e pesagem hidrostática

Abstract: A estimativa do percentual de gordura (%G) pela bioimpedância (BIA) tem como vantagem a simplicidade da medida. Contudo, a confiabilidade da BIA tem sofrido críticas. O objetivo deste estudo foi comparar a estimativa do %G através das técnicas de bioimpedância (RJL-101; Byodinamics A-310, Maltron BF-900 e BF-906), de dobras cutâneas (DC) e da pesagem hidrostática (PH). Observaram-se 25 indivíduos, homogeneizados segundo raça (branca), gênero (masculino) e idade (18 a 36 anos). Para a medida de BIA foi utilizad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1
14

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 15 publications
0
18
1
14
Order By: Relevance
“…his instrument demonstrated validity for the estimation of body fat with the hydrostatic weighing method 8,16 . he results of measurements revealed that the relative body fat (20.7 ± 7.6%) demonstrated by athletes in this study is above values desired for men (13 to 15%), but compatible with samples of wheelchair basketball players investigated by Gorla et al 17 (19.3 ± 8.4%, lower spinal cord injury, 23.4 ± 7.4%, upper spinal cord injury).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…his instrument demonstrated validity for the estimation of body fat with the hydrostatic weighing method 8,16 . he results of measurements revealed that the relative body fat (20.7 ± 7.6%) demonstrated by athletes in this study is above values desired for men (13 to 15%), but compatible with samples of wheelchair basketball players investigated by Gorla et al 17 (19.3 ± 8.4%, lower spinal cord injury, 23.4 ± 7.4%, upper spinal cord injury).…”
Section: Discussionmentioning
confidence: 99%
“…Participants were placed in dorsal decubitus on a stretcher and remained in rest for ive minutes. After this period, the instrument was turned on and immediately provided information on body composition such as fat, lean body mass and body water in relative (%) and absolute (kg) values, using equations already programmed by the instrument's manufacturer 8 .…”
Section: Body Compositionmentioning
confidence: 99%
“…This study was approved by the Ethics Research Committee of the Faculty of Philosophy Sciences and Languages of Ribeirão Preto -FF-CLRP (University of São Paulo USP). Data collection occurred with 66 older women, who were submitted to the following evaluations, in addition to those related to physical fitness: body mass and height measurement used a scale (graduation of 50g) with stadiometer (precision of 1.0 mm) (Welmy W200ALCD), body fat percentage used bioimpedance (Maltron BF-906) 18 , level of physical activity used the International Physical Activity Questionnaire (IPAQ ) (interview that assesses frequency in days and duration in minutes of activities performed for more than ten minutes continuously in a normal week, classified as intense, moderate and walking) 19 and assessment of the nutritional status by the Food Consumption Marker Form (indicates the frequency of consumption of 10 food groups in the days of a normal week) 20 . Although not included in the objectives, these two instruments were used because their results can interfere in the relations of genetic variations with body fat percentage and physical fitness -the other variables are important to characterize the sample.…”
Section: Samplementioning
confidence: 99%
“…Algumas investigações têm-se preocupado com a validação de técnicas a serem utilizadas na população brasileira, com a adoção de procedimentos mais precisos, visando a validar ou a analisar a concordância das equações antropomé-tricas 35 . Entretanto, não se observam estudos desse tipo com crianças e adolescentes.…”
Section: I S C U S S ã Ounclassified